Translating Jazz Into Poetry From Mimesis to Metaphor - Redling, Erik (Buchreihe der Anglia / Anglia Book Series, 2017)
The study develops a new theoretical approach to the relationship between two media (jazz music and writing) and demonstrates its explanatory power with the help of a rich sampling of jazz poems. Currently, the mimetic approach to intermediality (e.g., the notion that jazz poetry imitates jazz music) still dominates the field of criticism. This book challenges that interpretive approach. It demonstrates that a mimetic view of jazz poetry hinders readers from perceiving the metaphoric ways poets rendered music in writing. Drawing on and extending recent cognitive metaphor theories (Lakoff, Johnson, Turner, Fauconnier), it promotes a conceptual metaphor model that allows readers to discover the innovative ways poets translate "melody," "dynamics," "tempo," "mood," and other musical elements into literal and figurative expressions that invite readers to imagine the music in their mind’s eye (i.e., their mind’s ear)